2023
DOI: 10.1136/jitc-2023-007313
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I promotes immune evasion of colon cancer by modulating PD-L1 ubiquitination

Yangyang Zhang,
Lingxiu Zeng,
Meng Wang
et al.

Abstract: Colon cancer is one of the most prevalent cancers and exhibits high mortality worldwide. Despite the certain success in the immunotherapy of many tumor types, the limited response of colon cancer to immunotherapy remains a difficult problem. Retinoic acid-inducible gene-I (RIG-I) is a crucial component in innate antiviral immunity, but its role in antitumor immunity remains unclear. Here, in this report, we found that silencing RIG-I decreased resistance to tumor cells killed by T cells and attenuated colon tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Gao et al reported that Fusobacterium nucleatum , which is enriched in colorectal cancer tissues, upregulates the expression of PD-L1 by reducing the ubiquitination-mediated degradation of PD-L1 through IFIT1 [ 36 ]. RIG-I can compete with SPOP for binding to PD-L1, leading to reduced polyubiquitination and proteasome degradation of PD-L1 [ 37 ]. Ring finger protein 125 (RNF125) promotes ubiquitin-mediated degradation of PD-L1 and downregulates PD-L1 in oral squamous cell carcinoma (OSCC) TSCCA cells [ 38 ].…”
Section: Preclinical Study Of Ptms Inhibiting Pd-l1 Expression and Fu...mentioning
confidence: 99%
“…Gao et al reported that Fusobacterium nucleatum , which is enriched in colorectal cancer tissues, upregulates the expression of PD-L1 by reducing the ubiquitination-mediated degradation of PD-L1 through IFIT1 [ 36 ]. RIG-I can compete with SPOP for binding to PD-L1, leading to reduced polyubiquitination and proteasome degradation of PD-L1 [ 37 ]. Ring finger protein 125 (RNF125) promotes ubiquitin-mediated degradation of PD-L1 and downregulates PD-L1 in oral squamous cell carcinoma (OSCC) TSCCA cells [ 38 ].…”
Section: Preclinical Study Of Ptms Inhibiting Pd-l1 Expression and Fu...mentioning
confidence: 99%
“…RIG-I modulated SPOP-mediated degradation of PD-L1 and elevated immune evasion in colon cancer ( 101 ). Suppressing RIG-I led to a decrease in the ability of T cells to eliminate tumor cells and reduced the growth of colon tumors in mice with a fully functional immune system.…”
Section: Pd-1 and Pd-l1 Are Regulated By Ptmsmentioning
confidence: 99%
“…Intriguingly, RIG-I modulates the expression of PD-L1, facilitating immune escape in colon cancer independently of type I interferon activation. RIG-I prevents PD-L1 destruction by SPOP ( 101 ).…”
Section: Pd-1 and Pd-l1 Are Regulated By Ptmsmentioning
confidence: 99%
“…Foxp3, acting as a master switch for Treg, plays a crucial role in maintaining immune tolerance and suppressing autoimmunity, and is negatively correlated with colorectal cancer differentiation [20][21]. Furthermore, PDL1, known to reduce T-cell activation signals and facilitate immune evasion by cancer cells, emerges as a pivotal target for immunotherapy [22]. The outcomes revealed a signi cant increase in Foxp3, PDL1, CD8, GZMB, CD11b, MHC-I, and CD163 in the high-risk group, excluding CD68 (Fig.…”
Section: Exploration Of the Immune Microenvironment And Potential Drugsmentioning
confidence: 99%